Rare case of multiple splenic abscesses in enteric fever with contained rupture: Successful conservative management in an immunocompetent young adult - mishra, ananta; Manu, K. S.; Ananthakrishnan, R (Indian Journal of Case Reports, 2026)
Splenic abscess is a rare but potentially life-threatening complication of enteric fever, particularly in immunocompetent individuals. It occurs in